Distributional impacts of climate mitigation policies: A meta-analysis - Nils Ohlendorf; Michael Jakob; Jan Christoph Minx; Carsten Schröder; Jan Christoph Steckel (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Understanding the distributional impacts of market-based climate policies is crucial to design economically efficient climate change mitigation policies that are socially acceptable and avoid adverse impacts on the poor. Empirical studies that examine the distributional impacts of carbon pricing and fossil fuel subsidy reforms in different countries arrive at ambiguous results. To systematically determine the sources of variation between these outcomes, we apply an ordered probit meta-analysis framework. Based on a comprehensive, systematic and transparent screening of the literature, our sample comprises 53 empirical studies containing 183 effects in 39 countries. Results indicate a significantly increased likelihood of progressive distributional outcomes for studies on lower income countries and transport sector policies. The same applies to study designs that consider indirect effects, behavioral adjustments of consumers or lifetime income proxies. Future research on different types of revenue recycling schemes and lower income countries would further contribute to the literature.
Keywords: H23; Q52; Q58; 330; Meta-analysis; Environmental policies; Distributional impacts; Inequality; Climate change mitigation; Households; Environmental taxes; Redistribution; Poverty